PENGARUH BERBAGAI MACAN PERENDAMAN DAN KEDALAMAN PENANAMAN BENIH TERHADAP PERTUMBUHAN SEMAI MAHONI (Swietenia macrophylla) - Wahyu Saputra; Basir Achmad; Adistina Fitriani (Jurnal Sylva Scienteae, 2023)
The purpose of this study was to examine the survival percentage, height growth, and diameter growth of mahogany (Swietenia macrophylla) seedlings. The research method used was a factorial completely randomized design with 2 factors. The first factor consisted of five levels of immersion (control, young coconut water for 12 hours, onion solution for 6 hours, bean sprouts solution for 12 hours, and hot water 60°C for 12 hours). The second factor is the depth of planting with two levels of depth (1 cm and 2 cm). The research data were first analyzed for normality using the Kolmogorov-Smirnov test, followed by analysis of variance, Least Significance Different test, and Duncan’s multiple test. The results showed that there was a relationship between planting depth and immersion had a significant effect on the percentage of germination. Seeds planted two centimeters deep and soaked in various materials had the highest germination rates. The relationship between the immersion treatment and planting depth also had a significant effect on the growth of seedling height. The interaction of soaking treatment using bean sprouts solution for 12 hours at a depth of 2 cm resulted in the highest height growth (27.70 cm), while the treatment interaction that resulted in the lowest height growth (11.20 cm) was soaking with onion solution for 6 hours at 1 cm deep. Diameter growth is also significantly affected by this interaction. Soaking with bean sprouts solution for 12 hours at a planting depth of 2 cm resulted in the largest diameter growth (0.295 cm), while soaking with onion solution for 6 hours at a planting depth of 1 cm resulted in the smallest diameter growth (0.135 cm). The results of the study recommend that in order to obtain fast-growing seedlings, it is recommended to use bean sprouts soaking for 12 hours with a planting depth of 2 cm.Tujuan penelitian ini untuk menguji persentase hidup, pertumbuhan tinggi, serta pertumbuhan diameter dari bibit mahoni (Swietenia macrophylla). Metode penelitian yang digunakan ialah rancangan acak lengkap faktorial dengan 2 faktor. Faktor pertama terdiri dari lima tingkat perendaman (kontrol, air kelapa muda selama 12 jam, larutan bawang merah selama 6 jam, larutan tauge selama 12 jam, dan air panas 60° C selama 12 jam). Faktor kedua yaitu kedalaman tanam dengan dua tingkat kedalaman (1 cm dan 2 cm). Data penelitian terlebih dahulu dianalisis normalitasnya menggunakan uji Kolmogorov-Smirnov, dilanjutkan dengan analisis sidik ragam, uji beda nyata terkecil, serta uji berganda duncan. Hasil penelitian membuktikan bahwa ada hubungan antara kedalaman tanam dengan perendaman berpengaruh nyata terhadap persentase perkecambahan. Benih yang ditanam sedalam dua sentimeter dan direndam dalam berbagai bahan memiliki tingkat perkecambahan tertinggi. Hubungan antara perlakuan perendaman dan kedalaman tanam jugaberpengaruh nyata terhadap pertumbuhan tinggi semai. Interaksi perlakuan perendaman menggunakan larutan tauge selama 12 jam pada kedalaman 2 cm menghasilkan pertumbuhan tinggi paling tinggi (27,70 cm), sedangkan interaksi perlakuan yang menghasilkan pertumbuhan tinggi paling rendah (11,20 cm) adalah perendaman dengan larutan bawang merah selama 6 jam pada kedalaman 1 cm. Pertumbuhan diameter juga berpengaruh nyata oleh interaksi tersebut. Perendaman dengan larutan tauge selama 12 jam pada kedalaman tanam 2 cm menghasilkan pertumbuhan diameter terbesar (0,295 cm), sedangkan perendaman dengan larutan bawang merah selama 6 jam pada kedalaman tanam 1 cm menghasilkan pertumbuhan diameter terkecil (0,135 cm). Hasil penelitian merekomendasikan agar memperoleh pertumbuhan bibit yang cepat tumbuh disarankan menggunakan perendaman larutan tauge selama 12 jam dengan kedalaman tanam 2 cm.